Construction sectors efficiency analysis on seven European countries - Murillo, Kelly Patricia (2019)
Purpose – The purpose of this paper is to measure and compare the technical efficiency of construction companies in seven European countries: Austria, Germany, Hungary, Italy, Poland, Portugal and Spain, during the 2008–2015 period. The analysis involves nine sectors grouped into three divisions: construction of buildings (F41), civil engineering (F42) and specialized construction activities (F43), by NACE classification. Design/methodology/approach – Multidirectional efficiency analysis was adopted to investigate the levels of efficiencies, the differences in those levels and the possible causes of such differences by further defining two new indices. Findings – It showed that F43 is the most efficient division during the study period, followed by F42 and F41. The sectors/countries with less efficiency are: construction of roads and railways/Poland, construction of other civil engineering projects/Hungary, demolition and site preparation/Poland, other specialized construction activities/Portugal. Globally, the development of building projects sector uses resources in the most inefficient way and there was a drop in the efficiency in 2011 and 2013, showing a delay in the crisis impact. After 2010, civil engineering projects required a substantial effort to access resources. Other features regarding (in)efficiency were further identified. Originality/value – The analysis was conducted with one of the most effective techniques in frontier analysis. The first introduced index allows for comparing efficient/inefficient subgroups, and the other index measures the resource acquisition effort, allowing a better comparison along years. The study provides a good understanding of the performance of the construction industry and indirectly exposes the strategies to overcome the crisis, through the identification of the inputs/outputs which are well/badly used.